Novel 1,3,4-Oxadiazole Induces Anticancer Activity by Targeting NF-κB in Hepatocellular Carcinoma Cells - Mohan, Chakrabhavi Dhananjaya; Anilkumar, Nirvanappa C.; Rangappa, Shobith; Shanmugam, Muthu K.; Mishra, Srishti; Chinnathambi, Arunachalam; Alharbi, Sulaiman Ali; Bhattacharjee, Atanu; Sethi, Gautam; Kumar, Alan Prem; Basappa,; Rangappa, Kanchugarakoppal S. (Frontiers in Oncology, 2018)
Aberrant activation of NF-κB is linked with the progression of human malignancies including hepatocellular carcinoma (HCC) and blockade of NF-κB signalling could be a potential target in the treatment of several cancers. Therefore, designing of novel small molecule inhibitors that target NF-κB activation of prime importance in the treatment of several cancers. In the present work, we report the synthesis of series of 1,3,4-oxadiazoles, investigated their anticancer potential against HCC cells and identified 2-(3-chlorobenzo[b]thiophen-2-yl)-5-(3-methoxyphenyl)-1,3,4-oxadiazole (CMO) as the lead compound. Further, we examined the effect of CMO on cell cycle distribution (flow cytometry), apoptosis (annexin V-PI-FITC staining) and phosphorylation of NF-κB signalling pathway proteins (IκB and p65) in HCC cells. We found that CMO induced antiproliferative effect in dose- and time-dependent manner. Also, CMO significantly increased the percentage of sub-G1 cell population and induced apoptosis. Furthermore, CMO found to decrease the phosphorylation of IκB (Ser 32) in the cytoplasmic extract and p65 (Ser 536) in the nuclear extract of HCC cells. It also abrogated the DNA binding ability and transcriptional activity of NF-κB. CMO induced the cleavage of PARP and caspase-3 in a time-dependent manner. In addition, transfection with p65 siRNA blocks CMO induced caspase-3/7 activation. Molecular docking analysis revealed that CMO interacts with interface of p50 and p65 proteins. Thus, we are reporting CMO as an inhibitor of NF-κB signalling pathway.